ANALISIS METODE PERAMALAN (FORECASTING) PENJUALAN SEPEDA MOTOR HONDA DALAM MENYUSUN ANGGARAN PENJUALAN PADA PT TRIO MOTOR MARTADINATA BANJARMASIN - Sri Mulyani; Diana Hayati; Ayu Novita Sari (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2021)
Abstract, The purpose of this research is to determine the forecasting of sales of Honda Motorcycles at PT Trio Motor Martadinata Banjarmasin and to determine the preparation of a sales budget so that the sales level is in accordance with the level of consumer demand, so that there is no excess or shortage of inventory. The method used in this research is a quantitative descriptive method. The source of data is obtained indirectly or through intermediary media, namely in the form of documentation such as sales report data for the last 5 years and motorcycle inventory data. The results of this research indicate that sales forecasting at PT Trio Motor Martadinata Banjarmasin in 2020 has increased from previous years, namely as many as 3250 units. So that the supply of motorbikes can be prepared in accordance with sales forecasting so that consumer demand can be fulfilled. As well as the sales budget for 2020 amounting to Rp.69,845,759,000, - this sales budget can be used as a guide in making decisions in business activities to sell Honda motorbikes at PT Trio Motor Martadinata Banjarmasin.